A Cross-Cultural Exploratory Study of Health Behaviors and Wellbeing During COVID-19 - Ruiz, Montse C.; Devonport, Tracey J.; Chen-Wilson, Chao-Hwa (Josephine); Nicholls, Wendy; Cagas, Jonathan Y.; Fernandez-Montalvo, Javier; Choi, Youngjun; Robazza, Claudio (Frontiers in Psychology, 2021)
This study explored the influence of the COVID-19 pandemic on perceived health behaviours; physical activity, sleep, and diet behaviours, alongside associations with wellbeing. Participants were 1140 individuals residing in the UK (n = 230), South Korea (n = 204), Finland (n = 171), Philippines (n = 132), Latin America (n = 124), Spain (n = 112), North America (n = 87), and Italy (n = 80). They completed an online survey reporting possible changes in the targeted behaviours as well as perceived changes in their physical and mental health. Multivariate analyses of covariance variance (MANCOVA) on the final sample (n = 1131) revealed significant mean differences regarding perceived physical and mental health ‘over the last week’, as well as changes in health behaviours during the pandemic by levels of physical activity and country of residence. Follow up analyses indicated that individuals with highest decrease in physical activity reported significantly lower physical and mental health, while those with highest increase in physical activity reported significantly higher increase in sleep and lower weight gain. UK participants reported lowest levels of physical health and highest increase in weight while Latin American participants reported being most affected by emotional problems. Finnish participants reported significantly higher ratings for physical health. The physical activity by country interaction was significant for wellbeing. MANCOVA also revealed significant differences across physical activity levels and four established age categories. Participants in the oldest category reported being significantly least affected by personal and emotional problems; youngest participants reported significantly more sleep. The age by physical activity interaction was significant for eating. Discussed in light of Hobfoll’s (1998) conservation of resources theory, findings endorse the policy of advocating physical activity as a means of generating and maintaining resources combative of stress and protective of health.